2020
DOI: 10.1016/bs.acdb.2020.05.006
|View full text |Cite
|
Sign up to set email alerts
|

The development and consequences of moral essentialism

Abstract: The author wishes to thank James Dunlea for his helpful comments on this paper. Work on this manuscript was supported by awards from the John Templeton Foundation and the Russell Sage Foundation. Any opinions expressed are those of the author alone and should not be construed as representing the opinions of either the John Templeton Foundation or the Russell Sage Foundation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 104 publications
(119 reference statements)
1
18
1
Order By: Relevance
“…Past work led to two competing possibilities regarding how views about the impact of punishment on moral character might differ among children and adults. On the one hand, elementary schoolers are typically more likely than adults to view the social world through an essentialist lens (e.g., Chalik et al, 2017; Heiphetz et al, 2017; Hussak & Cimpian, 2019; Taylor et al, 2009), including when reasoning about moral character (Heiphetz, 2019, 2020). In other words, elementary schoolers are typically more likely than adults to view human characteristics—including moral character—as unchangeable, innate, and rooted in biology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past work led to two competing possibilities regarding how views about the impact of punishment on moral character might differ among children and adults. On the one hand, elementary schoolers are typically more likely than adults to view the social world through an essentialist lens (e.g., Chalik et al, 2017; Heiphetz et al, 2017; Hussak & Cimpian, 2019; Taylor et al, 2009), including when reasoning about moral character (Heiphetz, 2019, 2020). In other words, elementary schoolers are typically more likely than adults to view human characteristics—including moral character—as unchangeable, innate, and rooted in biology.…”
Section: Discussionmentioning
confidence: 99%
“…Although both children and adults endorse the idea that essences exist (for a review, see Rhodes & Mandalaywala, 2017), elementary schoolers typically report more essentialist perspectives than do adults (e.g., Chalik, Leslie, & Rhodes, 2017; Heiphetz, Gelman, & Young, 2017; Hussak & Cimpian, 2019; Taylor, Rhodes, & Gelman, 2009). Crucially, recent work has documented age‐related decreases in essentialist reasoning within the moral domain (for a review, see Heiphetz, 2020). Such studies have shown that children are more likely than adults to attribute punishment to an internal “bad” essence (Dunlea & Heiphetz, 2020) and to perceive moral badness as arising from an internal, unchanging source (Heiphetz, 2019).…”
Section: How Might Age‐related Changes In Socio‐moral Cognition Shape Views About the Impact Of Punishment On Moral Character?mentioning
confidence: 99%
“…Such dynamics are not limited to Muppet Kids, as actual children also seek out information about why social phenomena occur from more knowledgeable social partners (Callanan & Oakes, 1992;Legare, Wellman, & Gelman, 2009;Lombrozo, 2012). Importantly, the types of information children hear about why an event occurs can shape their social cognition (e.g., their attitudes toward a given individual, Heiphetz, 2020;Rhodes & Mandalaywala, 2017). Extrapolating to the current example, any information that Alex might have provided for the reason behind his father's incarceration could have influenced Abby's and Rosita's attitudes toward Alex's father.…”
Section: Language Shapes Children's Attitudes: Consequences Of Internal Behavioral and Societal Information In Punitive And Non-punitive mentioning
confidence: 99%
“…To address this question, additional research into beliefs about evil will be important. Extant research has uncovered individual differences in beliefs about the existence of evil (Bastian et al, 2015;Webster and Saucier, 2013; see also Heiphetz, 2020;Martin and Heiphetz, in press).…”
Section: The Role Of Beliefs About Evil and The True Selfmentioning
confidence: 99%